2020
DOI: 10.3390/nu12020358
|View full text |Cite
|
Sign up to set email alerts
|

Breast Milk Iodine Concentration Is Associated with Infant Growth, Independent of Maternal Weight

Abstract: In breastfed infants, human milk provides the primary source of iodine to meet demands during this vulnerable period of growth and development. Iodine is a key micronutrient that plays an essential role in hormone synthesis. Despite the importance of iodine, there is limited understanding of the maternal factors that influence milk iodine content and how milk iodine intake during infancy is related to postnatal growth. We examined breast milk samples from near 2 weeks and 2 months post-partum in a mother-infan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…[85 (43,134)µg/L] and 12MPP [95 (51,169)µg/L] < 100µg/L. The use of iodine-containing supplements increased MUIC and BMIC only at 3MPP.…”
Section: µG/l] 6mppmentioning
confidence: 99%
See 1 more Smart Citation
“…[85 (43,134)µg/L] and 12MPP [95 (51,169)µg/L] < 100µg/L. The use of iodine-containing supplements increased MUIC and BMIC only at 3MPP.…”
Section: µG/l] 6mppmentioning
confidence: 99%
“…This study found that maternal supplementation is more effective in ensuring adequate infant iodine status and maintaining BMIC levels until at least six months postpartum 42 . Achieving adequate maternal iodine status throughout lactation is critical for infants' growth 43 and also optimal fetal neurodevelopment 44 .…”
Section: Iodine Sufficiency and Deficiency During The First Postpartum Yearmentioning
confidence: 99%
“…Despite the best criteria for assessing an infant's iodine status have not been established due to the difficulty of sample collection for urinary iodine in this age group, there is sufficient data suggesting that the iodine status of infants could be extrapolated from either breast milk or maternal urinary iodine concentrations (Dold et al, 2017; Nazeri, Dalili, et al, 2018). In a pilot study by Ellsworth et al, BMIC at 2‐week postpartum was positively associated with infants' weight‐for‐age and weight‐for‐length over the first year of life (Ellsworth, McCaffery, Harman, Abbott, & Gregg, 2020). This finding was similar to our study with a different technique for BMIC measurement.…”
Section: Discussionmentioning
confidence: 99%
“…As such, iodine requirements are better met through breastmilk. A recent study found that breastmilk iodine concentrations were not associated with pre-pregnancy weight, although maternal diet was not considered in the analyses [48]. In contrast, the Centers for Disease Control and Prevention advises that the recommended daily allowance is 290 μg iodine for breastfeeding women, and that a supplement is indicated for women who do not consume dairy products [49].…”
Section: Iodinementioning
confidence: 99%